Empirical Treatment of Highly Suspected Nontuberculous Mycobacteria Infections Following Aesthetic Procedures - Kim, Hyung Rok; Yoon, Eul Sik; Kim, Deok Woo; Hwang, Na Hyun; Shon, Yoo Seok; Lee, Byung Il; Park, Seung-Ha (Archives of Plastic Surgery, 2014)
Background Infection caused by nontuberculous mycobacteria (NTM) has been increasing. Awareness of this infection is crucial yet problematic. Delayed management may lead to destructive results. We empirically treated a series of patients with clinical suspicion of NTM infection prior to the identification of the pathogen.Methods A total of 12 patients who developed surgical site infections between January 2011 and February 2014 were reviewed. Patients with a skin and subcutaneous infection resistant to standard management over two weeks, and previous history of aesthetic procedures within three months were regarded as highly suspected of having an NTM infection. A variety of diagnostic modalities were examined simultaneously, along with starting empirical treatment including a combination of clarithromycin and moxifloxacin, and surgical debridement.Results All wounds healed completely within 4 weeks. The mean follow-up duration was 7.2 months, and none of the patients developed relapse. Specific NTM pathogens were identified in six patients. Eight patients showed caseating granuloma implying an NTM infection. One patient showed an uncommon Stenotrophomonas infection, which was successfully treated. Three patients had no evidence of a pathogen despite repeated microbial tests. Complications such as scarring, pigmentation, and disfigurement were common in all the patients.Conclusions NTM should be considered in the differential diagnosis of an unusual skin and soft-tissue infection. We propose an empirical regimen of clarithromycin and moxifloxacin as an efficient treatment option for an NTM infection.
Keywords: Mycobacterium infections, nontuberculous; Soft-tissue infections; Early diagnosis; Antibiotics, antitubercular